Pengaruh Pengetahuan Perpajakan, Sanksi Pajak dan Peran Aparatur Desa Terhadap Kepatuhan Wajib Pajak - Sarani, Sarani; Terzaghi, M. Titan; Fitriasuri, Fitriasuri (Universitas Muhammadiyah Metro, 2024)
This research aims to provide an understanding of taxpayer compliance with non-compliance in paying PBB. Research method used: Selection of population and sample using simple random sampling, using quantitative data. Meanwhile, the data sources are primary data and secondary data, with one dependent variable and three independent variables. Using analysis with quantitative descriptive statistical methods. Data quality testing was carried out using validity testing and reliability testing. Meanwhile, the next test uses multiple linear regression analysis, Partial Significance Test (t Test), Simultaneous Significance Test (F Test). The research results provide that tax knowledge has a positive and significant impact on taxpayer compliance in paying PBB. Tax sanctions have a positive effect on taxpayer compliance in paying PBB. And the role of village officials has a positive influence on taxpayer compliance in paying PBB. With the role of village officials, it will encourage higher levels of taxpayer compliance in paying PBB.